Antireflection: Fabrication of Periodic Nanostructure Assemblies by Interfacial Energy Driven Colloidal Lithography (Adv. Funct. Mater. 29/2014). (August 2014) - Dev, A.; Dev Choudhury, B.; Abedin, A.; Anand, S.
<x xml:space="preserve">Abstract</x> An interfacial energy‐driven colloidal lithography technique to fabricate periodic nanostructure ensembles from a solution phase is demonstrated by A. Dev et al. on page 4577. It exploits different interfacial forces to periodically trap a liquid precursor under a monolayer of colloidal silica spheres arranged on a Si substrate. Using this technique, circular and ring‐shaped patterns of ZnO nanowire ensembles and thin films are fabricated. The method described here can be adopted to make periodic patterns from a wide variety of soluble materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>